(untitled) (Research, Society and Development, 2023)
The fight against child sexual violence is an interdisciplinary work and teachers are an indispensable bridge for the identification of cases. The present work aimed to analyze the level of knowledge of teachers of the basic school system on the theme. The quali-quantitative research was divided into two moments: application of an initial questionnaire via Google Forms to analyze the teacher’s prior knowledge; and conducting an open short course via Google Meet directed to the teaching role in this fight, with feedback questionnaire at the end. In the first questionnaire, 53 answers were analyzed, in which it was possible to identify that the participants did not have much contact with the theme during life. In the short course, 26 people were attended and, during the feedback, the interest and importance that the participants gave to the theme was noticeable. However, short time prevents the subject from being worked on more deeply and, therefore, it is necessary that themes like this are included in the initial teacher training, in order to teachers to be able to deal with adversity in the classroom.